The ratio of vision to data: Promoting emergent science and technologies through promissory regulation, the case of the FDA and personalised medicine. Issue 3 (27th October 2020) - Hogarth, Stuart; Martin, Paul
Abstract: Pharmacogenetic tests provide genetic data to tailor drug treatment and were widely predicted to be one of the first fruits of the Human Genome Project. In the mid‐2000s, the US Food and Drugs Administration (FDA) became an advocate for pharmacogenetic testing, but its efforts to build a market for this new technology brought the agency into dispute with other regulatory actors over the type of evidence needed for the adoption of pharmacogenetic testing, in particular the importance of randomized control trials. The warfarin case highlights the tension between a new form of promissory regulation driven by future expectations and FDA's established role as protector of public health; and the controversy can be conceptualized as a struggle over regulatory epistemologies within a complex polycentric regulatory space. Our case study addresses two themes central to the burgeoning scholarship on the governance of emergent science and technologies (EST): the political economy of regulation, in particular the role that regulators play in creating markets for EST; and the epistemological politics of regulatory science, in particular the controversy that arises when regulators modify scientific standards to accommodate EST. Linking these two themes is the concept of promissory regulation: the idea that regulatory policy may be shaped by an institutional commitment to the transformational potential of EST. This concept sheds new light on the neo‐mercantilist nature of contemporary regulatory capitalism.